A Study on the Psychological Characteristics of Rural Life on the Continuity of Rural Life (Medico Legal Update, 2019)
Interest and care for the people around the farming village to maintain the continuity of rural life. Efforts arealso needed to create younger farming villages by providing various facilities of convenience to help ensurethe young people’s settlement for rural life and also by organizing communities for those pursuing rural life.In addition, since pursuing rural life, it will be necessary to secure the profitability of crops by continuouslyparticipating in various agricultural education and visiting farming villages in advanced countries for securingeconomic power. The government and local governments will need to provide all facilities which help allpeople to easily settle for rural life by creating an environment similar to the cities through the environmentalimprovement projects of farming villages. Those pursuing rural life will need to explore various ways ofcommunicating with their family and offer them opportunities to experience farming.